Pengaruh Harga, Promosi, Kualitas Produk Terhadap Minat Beli Ulang Produk Kopi Kenangan pada Mahasiswa Fisip Unmul - M. Said (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of price, promotion, and product quality on the repurchase intention of Kopi Kenangan products among students of the Faculty of Social and Political Sciences, Mulawarman University. The research focuses on how effective marketing strategies can foster customer loyalty toward local coffee brands. The theoretical framework is based on the marketing mix, consumer decision-making processes, and indicators of customer loyalty. The study employs a quantitative research method, with data collected through questionnaires distributed to 100 respondents. The respondents were selected using purposive sampling, based on specific criteria determined by the researcher to ensure they could provide relevant information aligned with the research objectives. Data analysis was conducted using multiple linear regression with SPSS version 26. The findings indicate that price, promotion, and product quality each have a positive and significant effect on repurchase intention. Among these factors, product quality exerts the strongest influence, followed by promotion, and finally, price. These results suggest that enhancing product quality, implementing effective promotional strategies, and maintaining reasonable pricing can significantly increase customers’ likelihood of making repeat purchases. Based on the results, this study recommends that Kopi Kenangan continue to prioritize maintaining high and consistent product quality, as it plays a crucial role in shaping repurchase intentions. Additionally, promotional efforts should be continuously optimized to attract and retain customers in an increasingly competitive coffee market. Pricing strategies should also be monitored to remain competitive while ensuring profitability. Overall, the study concludes that product quality, supported by strategic promotions and competitive pricing, is essential for building and sustaining customer loyalty. By focusing on these factors, Kopi Kenangan can strengthen its market position and foster long-term relationships with its customers